Suppression of spectinomycin resistance in a mutant of Escherichia coli K-12. - Berg, P E (1975)
A mutant of Escherichia coli has been isolated which exhibits partial suppression of spectinomycin resistance. The site of mutation is in the streptomycin (strA) region and is closely linked to the spcA gene. However, this gene, which we propose to call mod, is phenotypically distinguishable from both the neomycin-kanamycin (nek) and the ribosomal ambiguity gene (ram). The relative gene order is mod spcA strA. In a cell-free protein synthesizing system, altered ribosomes appear to be responsible for the suppression of spectinomycin resistance caused by mod.